2015
DOI: 10.1002/2015gc006050
|View full text |Cite
|
Sign up to set email alerts
|

Deep subsurface carbon cycling in the Nankai Trough (Japan)—Evidence of tectonically induced stimulation of a deep microbial biosphere

Abstract: The abundance of microbial life and the sources of energy necessary for deep subsurface microbial communities remain enigmatic. Here we investigate deep microbial processes and their potential relationships to tectonic events in sediments from the Nankai Trough offshore Japan, drilled and sampled during IODP (Integrated Ocean Drilling Program) Expedition 316. Observed methane isotope profiles indicate that microbially mediated methane production occurs at Sites C0006 and C0007 in sediments below 450 meters bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 68 publications
(110 reference statements)
0
4
0
Order By: Relevance
“…Several studies on deep subseafloor sediments show that organic matter that is highly refractory at seafloor temperature (∼2-3°C) becomes accessible for microbial processes with increasing burial and related heating of the sediments (Burdige, 2011;Parkes et al, 2007;Wellsbury et al, 1997). Riedinger et al (2015) suggested that frictional heating associated with earthquakes might reactivate recalcitrant organic matter in deep sediments from IODP Sites C0006 and C0008 in the Nankai Trough, resulting in the onset of methanogenesis several hundred meters below the seafloor. Although, we cannot provide evidence on the reactivity of the organic material, we hypothesize that the higher temperatures prevailing since ∼0.5 Ma increased the bioavailability of organic matter at Site C0023, which caused enhanced rates of biogenic methanogenesis and higher methane fluxes in both, up-and downward directions.…”
Section: Elevated Organic Carbon Burial High Sedimentation Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies on deep subseafloor sediments show that organic matter that is highly refractory at seafloor temperature (∼2-3°C) becomes accessible for microbial processes with increasing burial and related heating of the sediments (Burdige, 2011;Parkes et al, 2007;Wellsbury et al, 1997). Riedinger et al (2015) suggested that frictional heating associated with earthquakes might reactivate recalcitrant organic matter in deep sediments from IODP Sites C0006 and C0008 in the Nankai Trough, resulting in the onset of methanogenesis several hundred meters below the seafloor. Although, we cannot provide evidence on the reactivity of the organic material, we hypothesize that the higher temperatures prevailing since ∼0.5 Ma increased the bioavailability of organic matter at Site C0023, which caused enhanced rates of biogenic methanogenesis and higher methane fluxes in both, up-and downward directions.…”
Section: Elevated Organic Carbon Burial High Sedimentation Environmentmentioning
confidence: 99%
“…In addition to variations in organic matter quantity and reactivity related to oceanographic and climatic changes, changes in biogeochemical processes can also be induced by tectonic dynamics including fluid flow along faults, hydrothermal circulation and frictional heating (e.g., Fischer et al., 2013; Wehrmann & Riedinger, 2016). For example, recalcitrant organic matter in subseafloor sediments from the Nankai accretionary prism might be reactivated caused by frictional heating associated with earthquakes or advective fluid flow (Ijiri et al., 2018; Riedinger et al., 2015). Marine sediments represent one of the most valuable archives to reconstruct changes in paleoceanographic, depositional and climatic conditions over Earth's history.…”
Section: Introductionmentioning
confidence: 99%
“…The establishment and propagation of the sediment-hosted deep biosphere is still under investigation, but likely includes a combination of selection from the surface environment (71) and persistence of cells with depth (72). What stimulates the deep biosphere, in addition to chemical interfaces, may include the continued influence of depositional conditions (68), tectonic activity (73), geological shifts under pressure (74), and the internal heating of Earth (75). It is still unknown exactly how the community in deep sediment responds to the stress of sedimentation.…”
Section: Sub-seafloor Sedimentsmentioning
confidence: 99%
“…Little is known, however, about the changes in deep subsurface systems of yearly or longer timescales. It may be possible that deep biosphere organisms persist with little to no growth until a rare nutrient or energy delivery, perhaps mediated by tectonic disturbance (Riedinger et al, 2015). Controlled substrate addition experiments performed in situ offer a novel experimental approach to understand the influence of transient energy influx on deep biosphere community structure and help constrain the energy requirements and maximum metabolic rates of these organisms.…”
Section: Introductionmentioning
confidence: 99%